2016
DOI: 10.1080/19415257.2016.1180316
|View full text |Cite
|
Sign up to set email alerts
|

Teacher agency and professional learning communities; what can Learning Rounds in Scotland teach us?

Abstract: Recently there has been growth in researching teacher agency. Some research has considered the relationship between teacher agency and professional learning. Similarly, there has been growing interest in professional learning communities as resources for professional learning. considering what factors might affect the utilisation (or otherwise) of affordances for teacher agency.The paper concludes with several recommendations for developing effective professional learning communities as an affordance for teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 37 publications
2
28
1
6
Order By: Relevance
“…Moreover, to achieve useful outcomes, social learning processes should be designed in such a manner that professionals have sufficient resources to shape their own professional identity and work (Eteläpelto, Vähäsantanen, Hökkä & Paloniemi, 2014). This touches on the notion that if meaningful learning is to be achieved, it is crucial to acknowledge and promote agency, and negotiations on professional identity (Philpott & Oates, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to achieve useful outcomes, social learning processes should be designed in such a manner that professionals have sufficient resources to shape their own professional identity and work (Eteläpelto, Vähäsantanen, Hökkä & Paloniemi, 2014). This touches on the notion that if meaningful learning is to be achieved, it is crucial to acknowledge and promote agency, and negotiations on professional identity (Philpott & Oates, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the workplace, the most proactive forms of agency are enacted via creative initiatives and innovative suggestions for developing work practices, creating new work operations, and transforming the course of activities (Engeström, 2011;Harteis & Goller, 2014;Philpott & Oates, 2017;Vähäsantanen, 2015). Virkkunen (2006) used the term "transformative agency" to refer to the ability and actions of individuals and groups to transform their work practices.…”
Section: Professional Agency As a Part Of Learningmentioning
confidence: 99%
“…Thus, familiar social relationships and positive work experiences may be drawn upon to promote agentic activities for professional learning (Vähäsantanen, 2015). In a similar vein, Goller and Billett (2014) argued that the agentic utilisation and crafting of experiences are crucial for successful professional learning, and Philpott and Oates (2017) suggested that professional communities and dialogical practices serve as affordances for professional agency in learning (see also Ylén, 2017, this volume). Conversely, traditional power-based professional relationships can obstruct the enactment of professional agency in learning and working contexts (Lipponen & Kumpulainen, 2011;Paloniemi & Collin, 2012).…”
Section: Professional Agency As a Part Of Learningmentioning
confidence: 99%
See 2 more Smart Citations